Jane Austen’s Comic Vision and Her Use of Irony - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2021)
Irony in its broadest sense, is a rhetorical device, literary technique, or event in which what on the surface appears to be the case or to be expected differs radically from what is actually the case. In other words, the basic feature of irony is a contrast between reality and appearance. It can be categorized into different types, including verbal irony, dramatic irony and situational irony. These types of ironies are often used for emphasis in the assertion of a truth. Jane Austen uses all these ironies in her novels to show the comic vision of her life. She has used it as a neutral discoverer and explorer of incongruities. How to cite this article:  Priydarshi AK. Jane Austen’s Comic Vision and Her Use of Irony. J Adv Res Eng & Edu 2020; 5(3): 12-14. DOI: https://doi.org/10.24321/2456.4370.202012